1970
DOI: 10.1099/00221287-61-3-409
|View full text |Cite
|
Sign up to set email alerts
|

Pisatin Production by Tissue Cultures of Pisum sativum L.

Abstract: SUMMARYCallus tissues of Pisum sativum produced the phytoalexin pisatin when grown in axenic culture. Coconut milk, which was in the culture media, induced pisatin formation in pea leaf discs. Cultures which had been established for over 18 months showed a marked reduction in the ability to produce pisatin. Pisatin inhibited the growth of pea callus at low concentrations (5 to 10 ,ug./ml.), and may control callus tissue initiation and cellular necrosis during host-fungus interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Pisatin content of the untreated cell suspension increased approximately ten fold of the original value in a 72 hour period, and showed a marked decline thereafter. A similar observation was made with pea callus (Bailey, 1970). When a pea cell suspension was exposed to the elicitor (one mg glucose equivalent per 100 ml medium), the cell cultures responded with an increased production of pisatin (Fig.…”
Section: Accumulation and Metabolism Of Pisatinsupporting
confidence: 77%
“…Pisatin content of the untreated cell suspension increased approximately ten fold of the original value in a 72 hour period, and showed a marked decline thereafter. A similar observation was made with pea callus (Bailey, 1970). When a pea cell suspension was exposed to the elicitor (one mg glucose equivalent per 100 ml medium), the cell cultures responded with an increased production of pisatin (Fig.…”
Section: Accumulation and Metabolism Of Pisatinsupporting
confidence: 77%
“…sesamin and kobusin), and alkaloids (e.g. sanguinarine, berberin, aristolochic acid, and narciclasine; Bailey, 1970;Trifunovic et al, 2003;Ono et al, 2006;Evidente et al, 1983;Gardiner et al, 2008;Na et al, 2011;Hu et al, 2012;Nakagawa et al, 2012;Hara and Kurita, 2014). Interestingly, the bioactivity of berberin and coptisin has been linked to the dioxole group as a structural analog, but without this functional group (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Reported abiotic elicitors for phytoalexin accumulation include heavy metals, especially mercuric and cupric chloride (Hargreaves 1979), respiratory inhibitors (Cheema and Haard 1978), detergents and other chemicals (Bailey 1982), mechanical wounding (Yoshikawa 1978), partial freezing (Lyon and Albersheim 1982), and UV light (Hadwiger and Schwochau 1971). Davis et al (1986) reported that biotic and abiotic elicitors can act synergistically in stimulating phytoalexin accumulation.…”
Section: Discussionmentioning
confidence: 99%